THE INFLUENCE OF STREAMING PLATFORMS ON RELIGIOUS CONTENT CONSUMPTION: A REVIEW OF THE LITERATURE ON SOCIAL AND CULTURAL IMPACTS - Ika Dewi Sartika Saimima; Al-Amin (Adisam Publisher, 2025)
The proliferation of streaming platforms and social media has changed the pattern of religious content consumption in society, especially among the younger generation. Literature shows that platforms such as YouTube, Instagram, and TikTok facilitate access to interactive, visual, and digestible religious information, significantly improving religious understanding, practice, and identity in millennials and Gen Z. Besides expanding the reach of da'wah and strengthening the solidarity of virtual communities, these platforms also contribute to building a more moderate and inclusive religious identity. However, challenges remain in the form of the risk of spreading invalid information and the tendency towards extreme interpretations, so digital literacy and wise supervision are needed so that streaming platforms truly become effective instruments in supporting the strengthening of moderate and relevant religious understanding in the digital era.